MITOS ILUSTRASI FOTO FERDI SAMBO DALAM PEMBERITAAN MEDIA ONLINE - Nofrizaldi, Nofrizaldi; Alika, Shintia Dwi (ARTCHIVE: Indonesian Journal of Visual Arts and Design, 2023)
In today's information technology era, modern society is greatly spoiled by the ease of access to news. One of the information media is online media reporting, which offers news content in written form as well as color photo illustrations, making it easier for readers to understand the content of the news. However, photo illustrations as news content can sometimes be confusing, such as in the reporting of the premeditated murder committed by Ferdi Sambo. Therefore, it is important to deeply understand the meaning of the photo illustrations from the news content about Ferdi Sambo so as not to be trapped in a superficial interpretation of a news story. The interpretation of Ferdi Sambo's photo illustrations in online media uses a qualitative methodology with a semiotic approach by Roland Barthes regarding denotation and connotation meanings. The results of the analysis conducted on the photo illustrations of Ferdi Sambo in online media reporting indicate that some objectives and interests can be concluded as resistance or defense conducted through body gestures and fashion to address the case being faced.